Characterization of bacteriocin-like compounds produced by lactic acid bacteria isolated from South African red wines and sherry - Van Jaarsveld, Desmond Ernst,1964- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1991.